Adenine-Induced Chronic Renal Failure in Rats: A Model of Chronic Renocardiac Syndrome with Left Ventricular Diastolic Dysfunction but Preserved Ejection Fraction - Pavlos Kashioulis; Jaana Lundgren; Emman Shubbar; Lisa Nguy; Aso Saeed; Cecilia Wallentin Guron; Gregor Guron (Karger Publishers, 2018)
Background/Aims: Cardiovascular disease is the major cause of death in patients with chronic kidney disease (CKD). Rats with adenine-induced chronic renal failure (ACRF) develop severe renal insufficiency and metabolic abnormalities that closely resemble those in patients with uremia. The aim of the present study was to determine left ventricular (LV) morphology and function in rats with ACRF. Methods: Male Sprague-Dawley rats received either chow containing adenine or were pair-fed an identical diet without adenine (controls, C). After 9-13 weeks animals were anesthetized with isoflurane and cardiac function was assessed both by echocardiography and by LV catheterization. Results: Rats with ACRF showed increases in serum creatinine (323±107 vs. 33±5 µM, P< 0.05), mean arterial pressure (115±6 vs. 106±7 mmHg, P< 0.05) and LV weight (3.4±0.3 vs. 2.5±0.2 mg/kg, P< 0.05) vs. controls. Rats with ACRF had reduced early diastolic tissue Doppler velocities in the LV, enlarged left atrial diameter (4.8±0.8 vs. 3.5±0.4 mm, P< 0.05) and elevated LV end-diastolic pressure (15±5 vs. 8±1 mmHg, P< 0.01). Cardiac output was increased in ACRF rats (211±66 vs. 149±24 ml/min, P< 0.05) and systolic function preserved. In the LV of ACRF rats there were statistically significant (P< 0.05) increases in cardiomyocyte diameter, proliferation and apoptosis, while there was no difference between groups in fibrosis. Conclusion: Rats with ACRF develop LV hypertrophy and diastolic dysfunction while systolic performance was preserved. There was an increased hypertrophy and apoptosis of cardiomyocytes in the LV of ACRF rats. The cardiac abnormalities in ACRF rats resemble those in patients with CKD in which heart failure with preserved ejection fraction is common. Hence, this experimental model is well suited for studying pathophysiological mechanisms in chronic renocardiac syndromes.